Keterkaitan E-Service Quality Dan E-Recovery Service Quality Maskapai Penerbangan Air Asia Dengan Menggunakan Structural Equation Modelling - Anton Tirta Komara (STMIK Mardira Indonesia, Bandung, 2014)
Developments in information technology make a paradigm shift in the consumer wins , so the use of e-commerce was inevitable. The purpose of this study to determine the relationship of e - service quality by e -recovery service quality customer Airlines Air Asia. The study population is customer Air Aviation Services Asia which are members of the backpacker community 's and the study sample was taken as many as 349 people. This sample was taken by random sampling . Analysis of data using Structural Equation Modelling (SEM). The results showed that there is a close relationship between e-service quality relationship with e -recovery service quality customer Airlines Air Asia. So it is evident that e-commerece based services can be used as one of the company's strategy to improve its service. Keywords: e-service quality; e-recovery; e-commerce